HUBUNGAN TIPE KEPRIBADIAN BERDASARKAN TEMPERAMEN DENGAN TINGKAT MOTIVASI BELAJAR - Pringga Adityawan (Jurnal Ilmiah Kesehatan Media Husada, 2013)
Personality Type Based on Temperament in each individual can affect the way they make a perception and act. Motivation can be the factor in each individual which can affect the quality of students in education process. The objective of this research is to identify positive relationship between Personality Type Based on Temperament with Motivation Level of Study of Students JIK 2007 A. The researcher used correlative researchmethodamong variable with crossectional approach. Researcher used all population in JIK 2007 A which it is consist of 60 students with Total Sampling Method.Based on Fisher analytical method, the result showed p=0.033 (p<0.05), coefficient contingency 0,344 and R square 0,013. It means there is a relationship between personality types based on Temperament with Motivation Level of Study. Based on the result of this research, for nurse in education department, hoped they begin to include type of personality as one of aspect in education process. And For furthermore study, hoped researcher can develop a better motivation questioner related to type of personality